IRRIGATION NETWORK PERFORMANCE INDEX ANALYSIS CASE STUDY OF BANDAR SAPAN KAYU MANANG IRRIGATION AREA, SOLOK REGENCY - Yayan Oktiawan (Indonesia Journal of Engineering and Education Technology (IJEET), 2023)
Utilization of irrigation networks for rice fields in West Sumatra in 2021, is able to produce 1.317 million tons of rice with a harvested area of 272,392 hectares which is spread throughout the urban districts in West Sumatra. One of them, in Solok Regency. Rice production in Solok Regency has experienced a deficit from 2018 to 2021. Therefore, it is necessary to assess the physical performance index of the irrigation network in Solok Regency, whether the decline in rice production is caused by the poor performance of the irrigation network. Determination of the physical performance index value of irrigation networks refers to the Regulation of the Minister of Public Works and Public Housing no. 12/PRT/M/2015 Regarding exploitation and maintenance of irrigation networks by modifying the assessment of the performance index, the performance index category is divided into 5 categories: very good, good, moderate, bad and very bad. The assessment is carried out by reviewing and evaluating the physical irrigation network in each Irrigation Area in Solok Regency.The results of the evaluation and assessment of the physical performance of the irrigation network in the irrigation area in Solok Regency, Bandar Panjang Selayo Irrigation Area, the physical performance index of the irrigation network is 67.63% in the good category, the Bandar Pamujan irrigation area the performance index value is 62.56% in the good category, the Irrigation Area Batang Lembang performance index 59.57% in the medium category, Bandar Lawas Sirukam irrigation area 68.90% in good category, Muaro Danau irrigation area 59.02% in the medium category, Bandar Paneh Gadang Irrigation Area performance index 59, 25% in the medium category, the Bandar Sapan Kayu Manang Irrigation Area with a performance index of 47.64% in the medium category, the Bandar Bitungan Irrigation Area with a performance index of 67.47% in the good category and the Bandar Gadang Irrigation Area with a performance index of 64.51% in the good category. The priority in handling improvements to the physical irrigation network in Solok Regency is the Bandar Sapan Kayu Manang Irrigation Area, Muaro Danau Irrigation Area, Paneh Gadang Irrigation Area and Batang Lembang Irrigation Area. Evaluated irrigation.